2015
DOI: 10.7461/jcen.2015.17.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Practical Incidence and Risk Factors of Terson's Syndrome: A Retrospective Analysis in 322 Consecutive Patients with Aneurysmal Subarachnoid Hemorrhage

Abstract: ObjectiveTerson's syndrome, a complication of visual function, has occasionally been reported in patients with aneurysmal subarachnoid hemorrhage (SAH), however the factors responsible for Terson's syndrome in aneurysmal SAH patients have not yet been fully clarified. In this study, we report on potential risk factors for prediction and diagnosis of Terson's syndrome in the earlier stage of the disease course in patients with aneurysmal SAH.Materials and MethodsThe authors retrospectively analyzed the data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In one such retrospective report, Lee et al . reported that the incidence of Terson syndrome in a Korean hospital between 2007 and 2013 was 10.6% (34 of 332 patients with aneurysmal SAH) 8 , while Seif et al . reported that the incidence of Terson syndrome in a Canadian hospital from 2012 to 2013 was 21.7% (10 of 46 patients with spontaneous SAH) 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In one such retrospective report, Lee et al . reported that the incidence of Terson syndrome in a Korean hospital between 2007 and 2013 was 10.6% (34 of 332 patients with aneurysmal SAH) 8 , while Seif et al . reported that the incidence of Terson syndrome in a Canadian hospital from 2012 to 2013 was 21.7% (10 of 46 patients with spontaneous SAH) 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al . reported that, in aneurysmal SAH, the treatment method differed between patients with Terson syndrome and those without the syndome; endovascular coil embolization was significantly correlated with Terson syndrome diagnosis 8 . They hypothesized that cerebrospinal fluid release during microsurgical aneurysmal clipping may prevent increases in intracranial pressure, and that this may influence the occurrence of intraocular hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Terson syndrome (TS), first described by Moritz Litten in 1881 and named after the French ophthalmologist Albert Terson, is a relatively common complication after subarachnoid hemorrhage (SAH), with rates of 10.2-46% in the literature [1][2][3]. It refers to an intraocular hemorrhage, for example, into the subhyaloid or intraretinal layers of the retina, or a vitreous hemorrhage (VH) which represents 3-5% of cases in the literature [2,4,5].…”
Section: Introductionmentioning
confidence: 99%